WAR, TRAUMA, AND FEMINIST CONSCIOUSNESS IN KATOUH’S NOVEL AS LONG AS THE LEMON TREES GROW - Sulasih Nurhayati; Lutfi Istikharoh; Luna Nur Lestari (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2025)
This study aims to explore the intersection of war, trauma, and feminist consciousness in Zoulfa Katouh’s As Long as the Lemon Trees Grow (2022). Katouh is a Syrian-Canadian novelist who is concerned about empowering female victims of their war trauma The demonstration of the dynamic circumstances that suppress and challenge the protagonist, Salama, to navigate her gendered experiences during the Syrian civil war, makes the current study as intersectional study. Intersectionality is a common term that connects the involvement of race, gender, class, and sexuality, which complicates an individual’s experiences in certain situations. Using Hooks’ intersectional feminism and Herman’s feminist trauma theory, the analysis reveals how Salama’s suffering and resilience during the war may create a feminist consciousness that challenges both patriarchal oppression and Western misconceptions about Middle Eastern women. Using a qualitative textual analysis, this study selects and examines primary data from the novel to unfold the intersectionality. Key narrative moments were primarily gathered to uncover how Salama’s trauma differs from that of her male counterparts due to the gendered burdens she bears. The study ultimately shows that her experiences of post-traumatic stress disorder (PTSD) and hallucinations are mainly intertwined with societal expectations and moral responsibilities. This situates her in a dual role, as a caregiver and a freedom fighter, intensifying her psychological and social struggles. Despite this burden, Salama’s resistance to oppression and her active role in advocating for freedom, especially for women, may be considered as subversion against the dominant Western narratives that often regard Arab women as passive or voiceless. Her journey particularly exemplifies the transformative power of trauma, portraying that survival and resistance against the oppressive war are essentially feminist acts. Katouh's novel thus offers a fresh perspective on feminist resistance within the context of war, showing how trauma can catalyze empowerment and social change while also revealing that Salama’s exceptional survival cannot represent the many women whose suffering remains unheard and demands a more inclusive feminist response. This research contributes to broader discussions on gendered trauma in conflict zones and encourages further interdisciplinary and comparative studies to explore unexplored themes that may expose urgent humanitarian concerns affecting women in war-torn regions.